Systematic approach to cross-contamination risk management in the production of medicinal products - A. A. Dzerzhinskaya; A. A. Spiridonova; E. G. Khomutova (Разработка и регистрация лекарственных средств, 2022)
Introduction. Good Manufacturing Practice (GMP) requires drug manufacturers to apply risk management principles in their operations. One of the main risks to the quality and safety of pharmaceuticals is cross-contamination. The introduction of a systematic approach to contamination risk management requires manufacturers to make a comprehensive assessment of both production processes and the organization of production sites (premises, equipment, systems, etc.). Therefore, the transition to the current GMP requirements for operating production sites may require significantly higher financial and labor costs than for projected production facilities.Aim. Development of a scientifically based program and methodology for cross-contamination risk management for existing pharmaceutical industries, taking into account compliance with the harmonized GMP requirements of the Russian Federation and the EAEU and world practice.Materials and methods. In the course of the study, methods of risk management, analysis and systematization of data and a process approach were used.Results and discussion. The key aspects of the organization of the co-manufacturing of medicines are outlined. A step-by-step approach to risk management, involving a preliminary assessment of the conformity of a production organization with GMP requirements is described. The proposed scheme is aimed at ensuring the continuous functioning of the cross-contamination risk management process.Conclusion. The presented risk management methodology aims to conduct a proper assessment of the risks of cross-contamination for multiproduct pharmaceutical enterprises. This technique allows to identify areas that need improvement to ensure compliance of manufacturing sites with GMP requirements, which ultimately contributes to improving the quality of medicines.